Consequences of Pathogen Lists: Why Some Diseases May Continue to Plague Us - Brett-Major, David M. (Am J Trop Med Hyg, 2019)
The current strategy used by many funding agencies for determining how money is spent on research to help prevent infectious disease outbreaks is based on pathogen-specific priority lists. Listing disease threats provides focus for business and research planning conducive to specific goals of developing a drug, or a vaccine, or other particular product. But, this singular type of focus has consequences. This perspective explores the consequences of lists, and describes how parallel programming independent of disease lists that address what we need to do to prevent and mitigate emerging disease risks may provide benefits out of reach of a singular focus on what products we need to have.